Mechanisms of Severe Adductor Longus Injuries in Professional Soccer Players : A Systematic Visual Video Analysis - Jokela, Aleksi; Pasta, Giulio; Della Villa, Francesco; Abrantes, Arnaldo; Kalogiannidis, Dimitrios; Garcia-Romero-Perez, Alvaro; Marano, Marco; Skibinskyi, Dmitriy; Mazzoni, Stefano; Pruna, Ricard; Valle, Xavier; Lempainen, Lasse (SAGE PUBLICATIONS INC, 2025)
Background: Changing direction, kicking, reaching, and jumping have been found to be the primary mechanisms of adductor longus injury. No previous studies specifically analyzing severe adductor longus injury mechanisms using video analysis have been published.
Purpose: To systematically analyze video footage to describe the mechanisms of severe acute adductor longus injuries in male professional soccer players.
Study Design: Cross-sectional study; Level of evidence, 3.
Methods: A total of 20 professional male soccer players (median age, 27 years; range, 18-35 years) who experienced an acute adductor longus injury during a match between October 2017 and December 2023 were included. All analyzed injuries were severe, either complete adductor longus tendon ruptures or partial lesions resulting in an absence from soccer competition of >28 days. Two authors independently reviewed the injuries based on a comprehensive injury causation model. Factors analyzed included playing situation, player/opponent behavior, and biomechanical descriptions encompassing whole-body and joint movements/positions.
Results: Of the 20 included injuries, 13 (65%) were considered noncontact and 7 (35%) were indirect contact. A closed kinetic chain (CKC) injury mechanism was found in 14 injuries (70%), an open kinetic chain (OKC) mechanism was found in 3 injuries (15%), and the injury occurred during high-speed running in the remaining 3 cases (15%). Player actions at the time of injury included reaching with the uninjured leg (CKC stretching; n = 11 [55%]), reaching with the injured leg (OKC stretching; n = 2 [10%]), dribbling (n = 2 [10%]), and landing (n = 2 [10%]). In CKC injuries, hip extension, hip abduction, and external rotation were all found in 64% of the cases. All OKC injuries involved hip abduction, external rotation, and rapid change of movement from hip extension to flexion.
Conclusion: Severe adductor longus injuries occurred predominantly during CKC actions, particularly when reaching for the ball with the uninjured leg. These injuries were consistently characterized by a combination of hip extension, abduction, and external rotation. A crucial aspect in these injuries appears to be the involvement of an eccentric muscle action, featuring rapid muscle activation during rapid muscle lengthening.